Financial Management in the Period of the Emirate of East Jordan between 1926 and 1939 AD "Hashemite documents as a source" - Zaher, Ehab Mohammad Ali (Jordan Journal for History and Archaeology, 2023)
How finances were managed in the Emirate of Transjordan between 1926-1939 CE is an important detail in the building of state institutions in the Emirate. Through the collection and analysis of data reported in the Hashemite documents (the papers of King Abdullah bin Al Hussein), the article highlights the financial management of the Emirate of Transjordan and those working in financial management, by examining the administrative measures used in preparing the budget and monitoring expenditures and revenues and how they developed. The article examines the development projects that were supported by the state finances of the Emirate of Transjordan, in the fields of transportation, health, construction, agriculture, water, and energy, based on collecting historical material from documentary and contemporary sources and newspapers. The finances of the Emirate, supervised by the executive council, showed that expenditures and revenues increased with each new fiscal year, reflecting the development and growth of the Emirate of Transjordan after the 1920s, and the accompanying emergence of new expenditures and new sources of income